Genome-wide association study of telomere length among South Asians identifies a second RTEL1 association signal. Issue 1 (18th November 2017) - Delgado, Dayana A; Zhang, Chenan; Chen, Lin S; Gao, Jianjun; Roy, Shantanu; Shinkle, Justin; Sabarinathan, Mekala; Argos, Maria; Tong, Lin; Ahmed, Alauddin; Islam, Tariqul; Rakibuz-Zaman, Muhammad; et al.
Abstract : Background: Leucocyte telomere length (TL) is a potential biomarker of ageing and risk for age-related disease. Leucocyte TL is heritable and shows substantial differences by race/ethnicity. Recent genome-wide association studies (GWAS) report 10 loci harbouring SNPs associated with leucocyte TL, but these studies focus primarily on populations of European ancestry. Objective: This study aims to enhance our understanding of genetic determinants of TL across populations. Methods: We performed a GWAS of TL using data on 5075 Bangladeshi adults. We measured TL using one of two technologies (qPCR or a Luminex-based method) and used standardised variables as TL phenotypes. Results: Our results replicate previously reported associations in the TERC and TERT regions (P=2.2×10 −8 and P=6.4×10 −6, respectively). We observed a novel association signal in the RTEL1 gene (intronic SNP rs2297439; P=2.82×10 −7 ) that is independent of previously reported TL-associated SNPs in this region. The minor allele for rs2297439 is common in South Asian populations (≥0.25) but at lower frequencies in other populations (eg, 0.07 in Northern Europeans). Among the eight other previously reported association signals, all were directionally consistent with our study, but only rs8105767 ( ZNF208 ) was nominally significant (P=0.003). SNP-based heritability estimates were as high as 44% when analysing close relatives but much lower when analysing distant relatives only. Conclusions: In this first GWAS of TL in a South Asian population, we replicate some, but not all, of the loci reported in prior GWAS of individuals of European ancestry, and we identify a novel second association signal at the RTEL1 locus.